The system-structural approach to development of professional potential of employees of law enforcement bodies - Metlickij, Igor E. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In article the theoretical analysis of modern approaches to development of professional potential of employees of law enforcement bodies in foreign countries with the subsequent scientific study of possibility introduction positive ideas and concepts in the organisation of professional psychological preparation of employees of law enforcement bodies of Belarus taking into account preservation and respect of domestic achievements in the field of law and order protection is carried out. The characteristic of three national systems which provide vocational training of employees of law enforcement bodies from a position of the purposes, problems and functions of protection of the law and order is given. Distinctive lines of integration of «vocational training» and «vocational education» in a context of psychological maintenance of professional work of employees of law enforcement bodies are allocated.
Keywords: the employee of law enforcement bodies; vocational training; vocational education; professional psychological preparation